Alih Fungsi Lahan Pertanian yang Berbatasan dengan Area Puspem Kabupaten Badung: Tahun 2005-2015 - Wibawa Patra, Kadek Ary (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2017)
Badung Civic Center (Puspem) is an integrated centre for government offices located in Sempidi of Mengwi District. As the core facility for all public services available to people of Badung Regency, the presence of Puspem has brought indirect impacts on the development of its surroundings. One visible impact observed clearly here is the increasing scale of land used to fulfill the need for housing on the one hand, and the shrinking scale of agricultural land being turned into built areas, on the other. This research aims to identify land use changes that took place in agricultural land adjacent to Puspem site which is divided into four zones (zone A, B, C and D). Data was collected through a series of physical observation, interviews, and detailed literature study. A map on land use change was constructed for a periode of 2005-2015 which was then analyzed using a comparative method. Various phenomenons associated with every land use change occured in the studied area were also examined. This study shows that there was no land use change occurred in zone A, even though it is located in a strategic location on the northern side of Puspe m . It is understandable since the area is destined as a green zone . Meanwhile, the highest rate of land use change took place in zone D, which is located on the eastern part of Puspem and passed by two main roads. A total of 10,58 Ha has had its use changed, or 32,95% from a total of 32,10 Ha. The agricultural land conversion of zone D began with the development of a road which in turn has caused an increase in land economic value and consequently triggerred the transfer of land ownership from farmers to new owners. Keywords: land use change, agricultural land, Badung Civic Center  (Puspem)